Pentosan polysulfate induces low-level persistent prion infection keeping measurable seeding activity without PrP-res detection in Fukuoka-1 infected cell cultures - Hanae Takatsuki; Morikazu Imamura; Tsuyoshi Mori; Ryuichiro Atarashi (Scientific Reports, 2022)
Abstract Each prion strain has its own characteristics and the efficacy of anti-prion drugs varies. Screening of prion disease therapeutics is typically evaluated by measuring amounts of protease-resistant prion protein (PrP-res). However, it remains unclear whether such measurements correlate with seeding activity, which is evaluated by real-time quaking-induced conversion (RT-QuIC). In this study, the effects of anti-prion compounds pentosan polysulfate (PPS), Congo red, and alprenolol were measured in N2a58 cells infected with Fukuoka-1 (FK1) or 22L strain. The compounds abolished PrP-res and seeding activity, except for N2a58/FK1 treated with PPS. Interestingly, the seeding activity of N2a58/FK1, which was reduced in the presence of PPS, was not lost and remained at low levels. However, upon removal of PPS, both were gradually restored to their original levels. These results indicate that low-level persistent prion infection keeping measurable seeding activity is induced by PPS in a strain-dependent manner. Furthermore, for protein misfolding cyclic amplification (PMCA), the anti-prion effect of PPS decreased in FK1 compared to 22L, suggesting that the differences occur at the level of the direct conversion. Our findings demonstrate that the advantages of RT-QuIC and PMCA can be exploited for more accurate assessment of therapeutic drug screening, reflecting strain differences.